Natural ventilation measurements in a multi-room dwelling: Critical aspects and comparability of pressurization and tracer gas decay tests. (October 2021) - Frattolillo, A.; Stabile, L.; Dell'Isola, M.
Abstract: Ventilation in built environments is essential to guarantee a good indoor air quality and a reduced probability of infection related to virus transmission. Measuring ventilation-related parameters is not easy and currently two methods can be adopted: pressurization and tracer gas decay. The pressurization test measures the airtightness of the building, whereas the tracer gas decay test measures the actual (site- and climate-specific) air exchange rate. Finding a relationship amongst the results provided by the two tests would be very useful in view of an exhaustive characterization of the building ventilation, but it still remains an open challenge for the scientific literature. The present paper aims at investigating the criticalities in correlating the two methods; thus, an experimental campaign was performed in a multi-room dwelling performing both air permeability and air exchange rate measurements in the entire dwelling and in parts of it. A detailed uncertainty budget of the two methods was also carried out in order to perform metrological compatibility analyses. The results of the campaign highlighted that the actual air exchange rates of the dwelling present a huge variability (from <0.2 to almost 1 h -1 ) due to the weather conditions. Consequently, the conversion factor between the air exchange rates at 50 Pa, provided by the blower door tests, and the actual air exchange rates, obtained through the tracer gas decay tests, ranged from <20 to >100, with an exponential decrease as the wind velocity increases. Thus, adopting constant conversion factors could significantly overestimate the actual ventilation of the building. Highlights: Building ventilation measurement methods were compared and discussed. Air exchange rate presents a huge variability due to the wind condition. Wind velocity affects the relationship between airtightness and air exchange rate. Conversion factor decreases exponentially as a function of the wind velocity. The "rule of thumb" conversion could be misleading to get actual air exchange rate.